Study of Electrical Power Facilities and Measures for Planned Outages in Japanese Hemodialysis Clinics After the Great East Japan Earthquake. Issue 1 (30th October 2012) - Ishida, Kai; Sawa, Manami; Fujiwara, Kousaku; Hirose, Minoru; Tsuruta, Harukazu; Takeuchi, Akihiro; Ikeda, Noriaki
Abstract The Great East Japan Earthquake on 11 March 2011 caused major damage in northeastern Japan. The Kanto region experienced a massive electrical power shortage in the summer of 2011. A questionnaire was submitted to 354 hemodialysis clinics in Kanagawa prefecture and the Tokyo metropolitan area, excluding isolated islands, and 176 responses were analyzed (49.7%). The questions included evaluation of the availability of a private electricity generator, countermeasures in case of a planned outage, awareness of saving electricity, and improvement of safety of medical devices or electrical facilities after the earthquake. Only 12% of the clinics had private electricity generators and many clinics had no plans to introduce this facility. However, 96% of the clinics had established countermeasures to deal with a planned outage. Many clinics planned to provide dialysis on a different day or at a different time. All clinics had tried hard to establish procedures to save electricity in the summer of 2011, and 84% of the clinics had reconsidered and improved the safety of medical devices or electricity facilities after the earthquake. These results show that the awareness of crisis management was greatly improved in the wake of the earthquake.